STUDENT PERCEPTION ON THE USE OF DIGITAL COMIC IN LEARNING VOCABULARY: A CASE STUDY AT ONE TEACHER TRAINING INSTITUTIONS - Rizky Nur Hidayah; Nunung Fajaryani; Nely Arif (JELT (Jambi-English Language Teaching), 2024)
The purposes of this qualitative research are to explore how EFL learners perceive the use of Digital Comics in learning Vocabulary and explain how Digital Comics are used for learning Vocabulary. In doing the research, the researcher used a case study approach for the design to provide a rich source of data on individuals’ experiences. Four participants participated in this research and they met the inclusive criteria for the research, including the Active students of Universitas Jambi in English education Study program who used Digital Comic beyond the Classroom, students who used Digital Comic in English version (not in Bahasa), and willing to voluntarily participate in the research. In collecting the data, the researcher employed semi-structured interviews. The researcher used the Qualitative Data analysis by Miles and Huberman (1984) to analyze the data from participants. Miles and Huberman (1984) identified three subsequent steps in data analysis: Data reduction, Data display, and Conclusion. The results indicated that four themes in how EFL learners perceive the use of Digital Comics in learning Vocabulary were identified, including, 1) Comic as Entertaining Media; 2) Flexibility of Digital Comic; 3) Affordable cost of Comic use, and 4) Positive Attitude towards Digital Comic Engagement. This Research also revealed that there were five identified strategies used by EFL students in learning vocabulary through Digital Comic, including, 1) Learning through Visuals; 2) Guessing the Word; 3) Integration with Language Apps; 4) Students acquire informal vocabulary; 5)Note taking; 6) Word practicing in daily activities.